Case Study Dynamics Of Harmonization Of Relations Between Balinese Traditional Village Residents And Chinese Residents In Singaraja City - Emben, Ni Komang Ayu Sari; Utami, A. A. Istri Dewi Adhi; sawu, Antonius Nelson Tonda; Sukarya, I Made Pande; Widarma, Dewa Putu Pradita; Dewi, Ni Komang Candra; Sara, Ni Komang Yasoda Syosti; Kusumadewi, Ni Komang Verlie (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze and identify the dynamics of the relationship between the residents of the Bali Traditional Village and the Chinese population in Singaraja City, Bali. This study also focuses on several important things, namely: (1) Knowing and analyzing the harmonization of relations between the indigenous people of the Balinese Traditional Village and the Chinese population in Singaraja City, (2) Attitudes and behaviors between residents (Balinese and Chinese Traditional Villages), and (3) How to maintain harmony between communities. This research uses ethnographic methods and focuses on cases or phenomena that occur in the field. In addition, this study also uses a descriptive qualitative approach, so that later the results of the research will be described through deeper and more detailed descriptions and explanations. Some of the final results obtained in this study are: (1) Despite having different customary traditions, races, and beliefs, the residents of Balinese and Chinese Traditional Villages highly uphold harmony with each other, (2) The positive attitudes and behaviors reflected from both sides of the population strongly reflect high harmonization and tolerance, and (3) Both types of residents attach importance to mutual cooperation (nyama braya), solidarity, and very high tolerance.